The impact of illegitimate tasks on burnout syndrome in a healthcare system: A cross-sectional study - Jorge Moncayo-Rizzo; Geovanny Alvarado-Villa; Clara Cossio-Uribe (Elsevier, 2024)
Background: Burnout syndrome, characterized by physical, mental, and emotional exhaustion due to continuous exposure to high-stress work conditions, has been increasingly recognized as a serious occupational phenomenon, especially amongst healthcare professionals. Recent studies indicate that illegitimate tasks-activities unrelated to one's role are a significant factor contributing to burnout. However, given the variability of work environments across regions, these findings may not apply universally. Objective: To investigate the behavior of the relationship between burnout and illegitimate tasks among healthcare professionals in Guayaquil, Ecuador. Methods: We conducted a survey of 562 healthcare professionals, including physicians, nurses, and medical/nursing interns, employing the Copenhagen Burnout Inventory and Bern Illegitimate Task Scale. Regression models were developed to predict burnout levels based on multiple factors, including demographic characteristics, professional roles, and perceptions of illegitimate tasks. Results: We revealed a statistically significant positive correlation between burnout and illegitimate tasks, with correlation coefficients ranging from 0.320 to 0.588, with higher levels of illegitimate tasks leading to increased burnout. Interestingly, we also found that age and length of service were negatively correlated with burnout, suggesting that these factors may serve as protective elements against burnout. Conclusions: Illegitimate tasks had an impact on burnout amongst healthcare professionals and emphasized the need for organizational strategies aimed at better task management to mitigate burnout risk.